A new species, new host records and life cycle data for lepocreadiids (Digenea) of pomacentrid fishes from the Great Barrier Reef, Australia - Berilin Duong; Scott C. Cutmore; Thomas H. Cribb; Kylie A. Pitt; Nicholas Q.-X. Wee; Rodney A. Bray (Systematic Parasitology, 2022)
A new species of lepocreadiid, Opechonoides opisthoporus n. sp. , is described infecting 12 pomacentrid fish species from the Great Barrier Reef, Australia, with Abudefduf whitleyi Allen & Robertson as the type-host. This taxon differs from the only other known member of the genus, Opechonoides gure Yamaguti, 1940, in the sucker width ratio, cirrus-sac length, position of the testes, position of the pore of Laurer’s canal, and relative post-testicular distance. The new species exhibits stenoxenic host-specificity, infecting pomacentrids from seven genera: Abudefduf Forsskål, Amphiprion Bloch & Schneider, Neoglyphidodon Allen, Neopomacentrus Allen, Plectroglyphidodon Fowler & Ball, Pomacentrus Lacépède and Stegastes Jenyns. Phylogenetic analyses of 28S rDNA sequence data demonstrate that O. opisthoporus n. sp. forms a strongly supported clade with Prodistomum orientale (Layman, 1930) Bray & Gibson, 1990. The life cycle of this new species is partly elucidated on the basis of ITS2 rDNA sequence data; intermediate hosts are shown to be three species of Ctenophora. New host records and molecular data are reported for Lepocreadium oyabitcha Machida, 1984 and Lepotrema amblyglyphidodonis Bray, Cutmore & Cribb, 2018, and new molecular data are provided for Lepotrema acanthochromidis Bray, Cutmore & Cribb, 2018 and Lepotrema adlardi (Bray, Cribb & Barker, 1993) Bray & Cribb, 1996. Novel cox 1 mtDNA sequence data showed intraspecific geographical structuring between Heron Island and Lizard Island for L. acanthochromidis but not for L. adlardi or O. opisthoporus n. sp.